Development Of An Active Suspension System To Prevent Passenger Cars Rollover - محمد نزار; محمد ابراهيم خنيسي; ربيع حبيب (Latakia University Journal -Engineering Sciences Series, 2024)
Rollover is one of the most dangerous maneuvers that a vehicle may undergo at driving , and the main cause of most traffic accidents deaths . Therefore, this study presents a developed model of Double A-Arms Suspension System , designed specifically to prevent the rollover of passenger cars during critical cornering maneuvers . The developed suspension system distinguishes by its ability to control of its roll center position , by controlling the inclination angles of the upper transverse arms , and its ability to provide an increase in the vehicle track width , during the control of roll center position . A model of the developed suspension system was built within the MATLAB-Multibody modeling environment . All parameters of this model were set to be equivalent to the parameters of the “Double Wishbone Suspension” reference model, built for a traditional Double A-arms Suspension System in the same previous environment, and stored within the MATLAB example library. The reference and developed models were then tested under the same critical cornering maneuver conditions . The developed model showed an ability to avoid rollover , unlike the reference model . The developed model also retained its ability to provide a good level of vibration dampening .